Technology Implementation on Objectives and Key Results in PT. Pos Indonesia 2020-2024 Period - Tonggo Marbun; Sora Baltasar; Eeng Ahman (International Institute for Advanced Science & Technology (IIAST), 2025)
This study aims to evaluate the implementation of technology in supporting the Objectives and Key Results (OKR) system at PT. Pos Indonesia during the 2020–2024 period, as part of the transformation into a more agile company. In its efforts to undergo business transformation, PT. Pos Indonesia utilizes technology to support various strategic objectives, such as market share growth, digital transformation, operational efficiency, and the development of customer based services. The technologies implemented include digital applications such as PosAja and PosPay, ERP systems, big data analytics, cloud based data digitization, and work process automation. As an agile company, PT. Pos Indonesia focuses on flexibility, cross-team collaboration, and data driven decision making to quickly respond to market changes. Research results show that the implementation of technology successfully increased transparency, collaboration, and accountability in the execution of OKRs. This technology also supports operational efficiency, service modernization, and the optimization of digital-based human resource management. However, challenges such as limited technological infrastructure, adaptation to a technology based work culture, and the need for employee training remain obstacles that need to be addressed. With a comprehensive agile approach, PT. Pos Indonesia has shown initial success in integrating technology to support OKR, while also strengthening its capabilities in responding to challenges and opportunities in the digital era. Continuous efforts are needed to refine the implementation and drive more adaptive innovation in the future